Oprøret på lægterne - Bonde, Hans (Historisk Tidsskrift, 2013)
Rebellion in the StandsAt the Danish national stadium in 1941, on 5 June, Denmark’s annually celebrated Constitution Day, no less, the Viennese football team Admira demonstrated its Greater Germany superiority with a 4 to 1 victory over a select Copenhagen team, thereby triggering among the Danish spectators a demonstratively negative reaction to a highly politicized programme of athletic collaboration with the Germans, who for their part set great store in it as a manifestation of the Reich’s “peaceful occupation” of Denmark. Even before the game began, the locals jeered at the guest team as it presented itself with the Nazi salute. During and especially after the contest the German soldiers in the stands were subjected to humiliating jibs and even bodily assault. The fact that the Austrians won the game no doubt played a part in the negative mood, but this is hardly an adequate explanation of the disarray, since spectator culture at that time in the history of Danish athletics was characterized by remarkable forbearance. Contemporary testimony of both participants and observers confirms this.Resistance to the occupying power at the Danish national stadium had consequences: the cooperative policy in the sports arena faltered - to the deep regret of the Danish athletic organisations, it may be added; under German pressure the Minister of Justice was replaced; and the Danish police were reorganised. The episode was not only the first instance of an extensive spectator disturbance in the history of Danish athletics, but also the first notable example in Denmark of open, collective aggressiveness towards the German Occupation. It took place before the student street demonstrations against the government’s accession to the Anti-Comintern Pact at the end of November 1941, which is traditionally cited in the literature on the period as the start signal for collective Danish defiance.In interpreting these events the article draws attention to the affinities between forms of protest or uprising characteristic of political commitment and the more general attraction to involvement and passion in the sports arena. However different in intent and reflective verbalization, the action-oriented forms of expression that are particularly distinct in sporting events and masculine working class culture can, as this example shows, also function as a genuine means of political protest.Translated by Michael Wolfe